Repensando o patrimônio: novos dilemas e potencialidades nas políticas de preservação - Carolina Pereira Soares (2006)
This thesis investigates the issue concerning the extension of the concept of cultural heritage, which has been taking place especially along the second half of the twentieth century. It starts with an analysis of some international documents that guide the debate concerning theinheritance issue. Afterwards, our understanding of some key concepts are deepened and enriched in the light of the sociological reflection on multiculturalism. This theoretical investigation leads to the statement of three cases, which are intended to illustrate some of the dilemmas andpotentialities at stake in contemporary preservation policies.The thesis ends up defending the hypothesis that the heritage issue experiences nowadays a significant perspective switch. In this new framework, preservation policies are called to promotethe locally sustainable development, acting as social inclusion tools based upon respect to differences.